The impact of an interprofessional training ward on the development of interprofessional competencies: study protocol of a longitudinal mixed-methods study - Mink, Johanna; Mitzkat, Anika; Mihaljevic, André Leopold; Trierweiler-Hauke, Birgit; Götsch, Burkhard; Schmidt, Jochen; Krug, Katja; Mahler, Cornelia (BMC medical education, 2019)
Background: To meet the patients’ needs and to provide adequate health care, students need to be prepared for interprofessional collaborative practice during their undergraduate education. On interprofessional training wards (IPTW) undergraduates of various health care professions potentially develop a mutual understanding and improve their interprofessional competencies in clinical practice. To enhance collaboration of 6th-year medical students and nursing trainees in the third year of their vocational training an IPTW (Heidelberger Interprofessionelle Ausbildungsstation - HIPSTA) was implemented at the University Hospital Heidelberg, Germany. On HIPSTA future physicians and nurses take care of the patients self responsibly and in close interprofessional collaboration, supervised by facilitators of both professions. Although there are positive experiences with IPTWs internationally, little is known about the impact of IPTW on the acquisition of interprofessional competencies. For future interprofessional training and implementation of IPTWs evaluation of interprofessional learning and collaborative practice on Germany’s first IPTW is of high relevance. Methods: To evaluate the acquisition of interprofessional competencies the study follows a mixed-methods approach. Quantitative data is collected from undergraduate participants, staff participants and facilitators on HIPSTA (intervention group) and undergraduate participants and staff participants on a comparable ‘conventional’ ward without special interprofessional training (comparison group) immediately pre and post HIPSTA and, as follow-up, after three to six months (T0, T1, T2), using three questionnaires, namely the University of the West of England Interprofessional Questionnaire (UWE-IP), the Interprofessional Socialization and Valuing Scale (ISVS) and the Assessment of Interprofessional Team Collaboration Scale (AITCS). Qualitative data is gathered in form of interviews and focus groups based on semi structured guidelines, video recordings of handovers and overt non-participant observations of daily rounds. Quantitative data will be analysed in a longitudinal comparison, presented descriptively and tested with an analysis of variance. Qualitative data will be analysed deductively and inductively. Discussion: The results of the evaluation will give insight in undergraduates’, staff’s and facilitators’ experiences and their self-perception of competency development. In addition the results will help identify benefits, challenges and areas for modification when implementing and establishing similar interprofessional training wards.
Gesehen am 15.08.2019